Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Cumulative Review: 33

Answer

$x_{1}=0$ and $x_{2}=3$

Work Step by Step

Given $\sqrt{4-x} = x-2 \longrightarrow (\sqrt{4-x})^2 = (x-2)^2 \longrightarrow$ $4-x = (x-2)^2 \longrightarrow 4-x = x^2 - 4x + 4 \longrightarrow$ $x^2 - 4x +x + 4 -4 = 0 \longrightarrow x^2 -3x = 0$ $a=1, \ b=-3, \ c=0$ Using the quadratic formula $\dfrac{-b \pm \sqrt{b^2-4ac}}{2a} , $ we have: $\dfrac{-(-3) \pm \sqrt{(-3)^2-4\times 1\times 0}}{2\times 1} = \dfrac{3 \pm \sqrt{9-0}}{2} = \dfrac{3 \pm \sqrt{9}}{2} = \dfrac{3 \pm 3}{2}$ Therefore we have that $x_{1}= \dfrac{3 + 3}{2}= \dfrac{6}{2} = 3$ and $x_{2}= \dfrac{3 - 3}{2}= \dfrac{0}{2}= 0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.